Stratification of Domains Using Composite Estimation to Measure the Revenue Level of Small Businesses in Poland - Dehnel, Grażyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
To meet the growing demand for detailed, precise, accurate and timely estimation of entrepreneurship and economic conditions, it is necessary to systematically extend the scope of information provided by business statistics. In view of the policy aimed at reducing survey costs and burdens for business units, the only way in which this objective can be achieved is by modernizing survey methodology. One area where this kind research is being conducted are applications of indirect estimation based on auxiliary sources of information from administrative sources. Hence, the purpose of the study described in this article is to evaluate the precision of estimates of revenues of small businesses for domains defined by spatial aggregation and business classification by applying stratification in composite estimators based on information collected from administrative registers.